Pengaruh Penyuluhan Kesehatan terhadap Pengetahuan Ibu Hamil Trimester III tentang Metode Pembuatan Sayur Bening Daun Katuk sebagai Upaya Meningkatkan Produksi ASI - Sri Handayani; Yopi Suryatim Pratiwi; Nurul Fatmawati (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2023)
Less milk production is one of the causes of failure of exclusive breastfeeding in Indonesia. Milk production can be increased by using herbs, namely katuk leaves. Katuk leaves are usually processed into clear vegetables. However, milk production is still low. Therefore, this study aims to analyze the effect of health education on the knowledge of third-trimester pregnant women about the method of making katuk leaf clear vegetable as an effort to increase milk production. The method in this study was a quasi-experiment with a one group pretest – posttest design. The number of samples used in this study was the total population of pregnant women in the third trimester of 28 people. This research was conducted in August 2022 in Jempong Baru Village, Mataram City. Bivariate analysis uses the T-Test because the data is normally distributed with a significant value of 0.083>0.05. The results of the bivariate analysis showed that there was an effect of providing health education on the third trimester pregnant women's knowledge of the method of making katuk leaf clear vegetable with a p value <0.05 (p=0.006). In addition, there was an increase in the knowledge of pregnant women by 25% after being given health education. The conclusion in this study is that health education can increase pregnant women's knowledge about the method of making katuk leaf clear vegetable. It is recommended for pregnant women to increase knowledge about plant processing methods that can increase milk production so that breastfeeding mothers can give exclusive breastfeeding.